La Cartographie Participative en 3 Dimensions (CP3D) comme outil au service d’une gestion partagée des risques ? - Pauline Texier‑Teixeira; Floriane Chouraqui; Franck Lavigne; Delphine Grancher; Jake Rom Cadag; Jean‑Christophe Gaillard (Bulletin de l’Association de Géographes Français, 2014)
Within the framework of the 7th FP international research program entitled MIA VITA (Mitigate and Assess risk from Volcanic Impact on Terrain and human Activities), a tool for Disaster Risk reduction following an integrated participatory approach was proposed: the Participatory 3 Dimensions Mapping (P3DM). This tool represents the different levels of knowledge and competences of the stakeholders involved in the DRR at different scales. It is expected to help the mitigation by developing relevant discussions and cooperation between the top-down and the bottom-up approaches (e.g. between authorities and communities living on the slopes of the volcano). A case study from Fogo volcano (Cape Verde) addresses and discusses the major flaws of such participatory approach.